(untitled) (Bangladesh Agronomy Journal, 2017)
The study was conducted to determine the effect of nitrogen (N) and phosphorus (P) fertilizer on the physio-chemical changes in composition of jute seed under applied N and P Tossa jute (S.N.) cv. O-9897 was grown at five levels of nitrogen (0, 30, 60, 90 and 120 Kg N ha-1) and five levels phosphorus (0, 10, 20, 30, 40 Kg P ha-1) in late sown condition as seed crop. After harvesting seeds were categorized in to five groups viz. low vigour, medium low vigour, medium vigour, medium high vigour and high vigour which were used for analyzing the chemical composition of jute seed. Results revealed that the chemical composition of jute seed was changed under applied nutrient where combination of 120 kg N ha-1and 40 kg P ha-1 gave the highest soluble protein, soluble sugar and ash content while the lowest soluble protein, soluble sugar and ash content and the highest free amino acid and oil content were estimated from the treatment with no nitrogen and no phosphorus fertilizer. Bangladesh Agron. J. 2016 19(2): 29-38